Evaluation and improvement of isolation protocols of pathogenic Vibrio parahaemolyticus in frozen prawns / Salima Sadeghi - Salima , Sadeghi (2018)
The evaluation of different protocols for isolation and enumeration of Vibrio parahaemolyticus from frozen prawn samples were developed in this study. The selectivity of CHROMagar™Vibrio (CV) and Thiosulphate-citrate-bile salts-sucrose agar (TCBS) media for Vibrio parahaemolyticus were examined using different enrichment methods and incubation temperatures. Direct plating on CV at 37°C resulted in significantly higher counts of V. parahaemolyticus compared to direct plating on TCBS agar at lower temperatures (p<0.05). There was a significant improvement in selectivity on TCBS agar using an enrichment process. Virulent isolates of V. parahaemolyticus (tdh-/trh+) were only recovered from one prawn sample out of 20 frozen prawn packs (5%) when grown on CV agar. REP-PCR molecular typing demonstrated that CV isolated more genetically diverse V. parahaemolyticus than TCBS agar. The carbon consumption of V. parahaemolyticus, including pathogenic and non-pathogenic (tdh-/trh-) isolates was studied using a phenotype microarray system (BIOLOG). Carbon utilization in tdh+/trh-isolates were significantly different from other isolates. This assists in the development and improvement of selective media for effective isolation of foodborne pathogens. In conclusion, the findings suggest that CV is a better selective medium and is less inhibitive for the isolation and detection of V. parahaemolyticus particularly virulent isolates from frozen prawn samples. This current work also recommended that using a direct-plating method on CV at 37°C could be an efficient alternative to MPN-PCR for enumeration of V. parahaemolyticus from frozen prawn samples.